Z-effect after intramedullary nailing systems for trochanteric femur fractures - S.J.M. Smeets; G. Kuijt; P.V. van Eerten (Chinese Journal of Traumatology, 2017)
Purpose: The aim of this study was to investigate the incidence of Z-effect after dual lag screw intramedullary nailing systems and risk factors contributing to this effect. We hypothesized that long nails provide more neck strength due to a longer lever than short nails and are therefore less likely to develop a misbalance of a higher head compressive strength than neck compressive strength. Methods: In this retrospective cohort study 103 patients treated operatively with a dual lag screw intramedullary nailing device for (sub)trochanteric hip fracture were included. We analysed patient charts regarding patient and operation characteristics. Furthermore we conducted radiologic measurements within the 2-year follow-up period to investigate the quality of fracture fixation, implant failure and predictors for Z-effect. The re-operation risk was investigated with multivariate regression analysis. Results: The incidence of (reversed) Z-effect in this study was 9% (n = 80); 6 out of 7 Z-effects occurred in the short nail group, which was not significant. Patients who were treated with a long nail had a significant larger number of complications in comparison with the short nail group (median 2 vs 0.5, p = 0.001). The long nail group received more often erythrocytes blood transfusions (82% vs 31%, p < 0.01) and had a longer hospital stay (13 vs 21 days, p < 0.05). Migration of lag screws (p <0.05) and unstable fracture type (p < 0.05), were risk factors for re-operation. The re-operation rate within 2 year after surgery was 21%, of which one fourth was due to a Z-effect. Conclusion: The nail length was not associated with the development of a Z-effect. Migration of lag screws after intramedullary nailing is common and a risk factor for re-operation.